Air Quality Index Assessment Based on Crowdsourcing Data - Mirela Beca Ilinca; Cristian Toșa (Romanian Journal of Transport Infrastructure)
Air quality indicators offer qualitative insights into environmental conditions regarding the concentration of air pollutants. Among the most widely utilized indicators globally is the Air Quality Index (AQI), facilitating the evaluation of air pollution levels and its ramifications on health and natural ecosystems. The AQI relies on various calculation methods, which differ from country to country.